PENINGKATAN KETERAMPILAN PROSES SAINS SISWA SD PADA MATERI SUHU DAN KALOR MELALUI PEMBELAJARAN VAK - Rahmawati, Amalia; Jayadinata, Asep Kurnia; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
Based on the researcher's interest in the ability of students 'learning styles that can be used with Visual, Auditory, and Kinesthetic learning models (VAK) is an appropriate way to improve students' science process skills, so students can feel comfortable and not easily feel bored because rarely once the teacher in his learning activities uses all three learning styles. And based on the theory of Jean Paget, Accelerated Learning, and Bruner. The purpose of this study was to determine the improvement of students' science process skills in temperature and heat material through VAK learning. The design of this study was quasi-experimental with the population of all fifth grade elementary school students in Cimaung sub-district. The sample was SDN Jagabaya 02, VA class as the experimental class and VB class as the control class. The instruments used were science process skills tests, student response questionnaires, guidelines for observing student activities and teacher performance. Based on the results of the study, there were differences in the improvement of science process skills of students between those using the VAK model using conventional learning models.